After Dictatorship - Hoeres, Peter; Knabe, Hubertus (2023)
What must be done after the end of a dictatorship so that the suffering of those persecuted comes to an end and history does not repeat itself? Only rarely have long-term studies academically investigated the effects that measures implemented within the context of transitional justice have actually achieved. Taking seven countries as examples, this volume analyses what coming to terms with dictatorships can accomplish – and where its limits lie.